Desenvolvimento e implementação de um sistema de triagem no Hospital veterinário da UFMG - Ana Cláudia Campos da Fonseca (2021)
The triage came from military activities, which sought to save the largest number of soldiers in order to maintain military power on the battlefield. Over the years, triage has been implemented in human emergency departments and spreading throughout the Western world. In veterinary medicine, there is still no validated and recognized triage system, and the subject is not discussed in emergency departments. In most establishments, triage is carried out intuitively, prioritizing only those patients at imminent risk of life. Many veterinary medicine triage systems are adaptations of human systems and there is no work to prove the efficiency of implementing these systems in the routine of a department. The present work adapted the Manchester Screening System to a veterinary center and evaluated its benefits when it was implemented. A total of 553 animals and guardians participated in the study, 275 in the first phase and 278 in the second phase. The canine species was predominant in the study (84.8%) and the average age of the animals was 81.33 months. The most selected priority level was green (37.4% - phase 1 / 42% - phase 2), followed by the blue, yellow, red category (8.7% - phase1/ 7.5% - phase 2) and orange in both phases.The superiority of the new sorting system was notorious when compared to the intuitive sorting system. The developed triage system provided that a greater number of patients were screened, was better accepted by tutors and demonstrated greater clarity to tutors regarding the patients' state of severity. Further studies are needed to evaluate the efficiency and effectiveness of the triage systems in the veterinary routine, however their superiority to the intuitive triage system was evident.